IMPLEMENTASI MODEL PEMBELAJARAN INDUKTIF BERBANTUAN MEDIA POHON PUZZLE UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I UPTD SD NEGERI 27 PEUSANGAN - Tarini Mahbengi; Nurlaili; Nurmina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low early reading ability of first-grade students at UPTD SD Negeri 27 Peusangan, as indicated by the low level of learning mastery in the preliminary assessment. The study aimed to improve students' early reading ability through the implementation of the Inductive Learning Model assisted by the Tree Puzzle media, describe teacher and student learning activities, and examine students' responses to the learning process. This study employed a qualitative approach using Classroom Action Research (CAR), conducted in two cycles consisting of planning, action, observation, and reflection. The research participants were 28 first-grade students of UPTD SD Negeri 27 Peusangan. Data were collected through tests, observations, and interviews and analyzed using percentage analysis and descriptive qualitative techniques. The findings revealed that the implementation of the Inductive Learning Model assisted by the Tree Puzzle media effectively improved students' early reading ability. The mean score increased from 71.66 in the pre-test to 78.95 in Cycle I and 86.23 in Cycle II, with classical learning mastery reaching 100% in Cycle II. Teacher activity improved from 92.58% to 100%, while student activity increased from 91.93% to 100%. In addition, students' responses to the learning process were categorized as very positive. Therefore, the implementation of the Inductive Learning Model assisted by the Tree Puzzle media was effective in improving the early reading ability of first-grade students at UPTD SD Negeri 27 Peusangan.